Masyarakat Madani dan Tantangan Radikalisme - Muhammad Rizkon Fawa'id (Journal of Islamic Civilization, 2019)
Today the religious behavior of Indonesian Muslim youth with two different ideological foundations namely Radicalism and Pluralism. Radicalism is the understanding of individuals or groups with ways of thinking, behaving, and rooted behavior or totality in achieving certain goals while pluralism is a way of living by understanding the acceptance of differences, openness of thought and act of respect for others. in Medina at that time, there were still conflicts between groups that never lived. Sometimes some groups make use of religiosity as part of the effort to cover commodities. So that the frame about maintaining public morality and religion still needs to be united in the framework of mutual understanding between each other and helping each other on what the community really needs. The challenge of Islamic groups called fundamentalist, exclusive, and radical is indeed possible to bring Indonesia to a state of society far from civilization and humanity. So that the great potential of Indonesian Muslim youth with a plural attitude will be able to bring Indonesia to the Madani community. This is certainly not as simple as the discourse, but young Indonesian Muslims must be able to become initiators in the midst of a multidimensional crisis in society.